2015
DOI: 10.1016/j.ocemod.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian analysis of the vertical structure of eddies simulated in the Japan Basin of the Japan/East Sea

Abstract: The output from an eddy-resolved multi-layered circulation model is used to analyze the vertical structure of simulated deep-sea eddies in the Japan Basin of the Japan/East Sea constrained by bottom topography. We focus on Lagrangian analysis of anticyclonic eddies, generated in the model in a typical year approximately at the place of the M3 mooring (Takematsu et al., 1999) and the hydrographic sections (Talley et al., 2001), where such eddies have been regularly observed in different years (1993)(1994)(1995)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…This current meets the North Korean Cold Current, which is an extension of the Liman Cold Current. This northward-flowing warm, subtropical water meets southward-flowing cold, subarctic SOJ waters to form the polar front at approximately 40 • N. The SOJ is therefore divided largely into two regions (Prants et al, 2015). The current system in and around the SOJ should be taken into consideration when assessing the spatio-temporal variations in radiocaesium derived from global fallout and the FNPP1 accident.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This current meets the North Korean Cold Current, which is an extension of the Liman Cold Current. This northward-flowing warm, subtropical water meets southward-flowing cold, subarctic SOJ waters to form the polar front at approximately 40 • N. The SOJ is therefore divided largely into two regions (Prants et al, 2015). The current system in and around the SOJ should be taken into consideration when assessing the spatio-temporal variations in radiocaesium derived from global fallout and the FNPP1 accident.…”
Section: Introductionmentioning
confidence: 99%
“…Aeolian 137 Cs deposited south of the Kuroshio Extension was apparently subducted into the STMW and transported southwards within 10 months after the FNPP1 accident. Rossi et al (2013) have reported that simulated FNPP1-derived 137 Cs penetrated into the ocean interior via intense subduction and vertical mixing during the winter in the region of mode water formation as described by . Kamidaira et al (2018) have also reported that their model simulation reproduced relatively high 137 Cs activity concentration below the mixed layer.…”
Section: Introductionmentioning
confidence: 99%
“…1) and the eastward zonal jet blocking northward transport across it. Topographically constrained anticyclonic eddies with the centre at about 41-41.5 • N, 134-134.5 • E have been regularly observed there (Takematsu et al, 1999;Talley et al, 2006;Prants et al, 2015).…”
Section: Resultsmentioning
confidence: 94%
“…Prants et al [31] explicitly look at LCSs near Japan, but they were looking at ocean current in the Japan Basin which is on the west side of Japan. This paper has references to people in Haller's group and mentions LCSs in the writing.…”
Section: Fukushima: An Lcs Case Studymentioning
confidence: 99%